2017
DOI: 10.1186/s13014-017-0807-y
|View full text |Cite
|
Sign up to set email alerts
|

Setup errors in patients with head-neck cancer (HNC), treated using the Intensity Modulated Radiation Therapy (IMRT) technique: how it influences the customised immobilisation systems, patient’s pain and anxiety

Abstract: BackgroundIn patients with head-neck cancer treated with IMRT, immobility of the upper part of the body during radiation is maintained by means of customised immobilisation devices.The main purpose of this study was to determine how the procedures for preparation of customised immobilisation systems and the patients characteristics influence the extent of setup errors.MethodsA longitudinal, prospective study involving 29 patients treated with IMRT. Data were collected before CT simulation and during all the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The setup variability results indicate that immobilization in a custom thermoplastic head and neck mask resulted in highly reproducible patient positioning with setup errors consistent with values previously reported in the literature [29][30][31]. In both the ATP and ATS workflows of the Unity system, an adaptive plan cannot be created if the isocenter shift exceeds 5 cm in any one direction because the table can only be moved longitudinally along the y (superior/inferior) axis.…”
Section: Discussionsupporting
confidence: 83%
“…The setup variability results indicate that immobilization in a custom thermoplastic head and neck mask resulted in highly reproducible patient positioning with setup errors consistent with values previously reported in the literature [29][30][31]. In both the ATP and ATS workflows of the Unity system, an adaptive plan cannot be created if the isocenter shift exceeds 5 cm in any one direction because the table can only be moved longitudinally along the y (superior/inferior) axis.…”
Section: Discussionsupporting
confidence: 83%
“…Several investigators have reported that positional, anatomical and tumor alterations can occur during radiotherapy of HNSCC. These changes may prevent the prescribed dose delivery to tumor volumes and may cause significant toxicity by increasing the dose to the organs at risk (OARs) (6)(7)(8). Adaptive radiotherapy (ART) is an approach to mitigate the dosimetry effects of these changes (9).…”
Section: Introductionmentioning
confidence: 99%
“…The advancing knowledge about diseases and the increasing complexity of radiation planning and delivery methods can make radiation therapy vulnerable to errors. 1 A considerable variation in target volume delineation among radiation oncologists may occur, which can influence local tumor control and can result in undesirable complications in patients. 2 These differences exist despite adherence to well-established organ dose criteria and uniform contouring guidelines.…”
Section: Introductionmentioning
confidence: 99%